2003
DOI: 10.1189/jlb.0902454
|View full text |Cite
|
Sign up to set email alerts
|

The effect of phosphatases SHP-1 and SHIP-1 on signaling by the ITIM- and ITAM-containing Fcγ receptors FcγRIIB and FcγRIIA

Abstract: Inositol and tyrosine phosphatases have been implicated in inhibitory signaling by an Fc receptor for immunoglobulin G, FcgammaRIIB, in B cells, mast cells, and monocytes. Here, we propose a role for the Src homology 2 (SH2)-containing tyrosine phosphatase-1 (SHP-1) in FcgammaRIIB-mediated inhibition of FcgammaR signaling. Coexpression of SHP-1 enhances FcgammaRIIB-mediated inhibition of FcgammaRIIA phagocytosis in COS-1 cells. SHP-1 also enhances the reduction in FcgammaRIIA tyrosine phosphorylation that acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
74
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 30 publications
4
74
1
Order By: Relevance
“…SHIP-1 was first shown to associate with immunoreceptor tyrosine-based inhibitory motifs of inhibitory FcRIIB, which indicated that it normally inhibits phagocytosis [92]. SHIP-1 has recently been shown to associate with FcR containing ITAMs [17,93]; it is therefore possible that it contributes to phagosome formation by turning off PI(3,4,5)P 3 -dependent signals in the forming phagosome.…”
Section: Phagosomal Lipidsmentioning
confidence: 99%
See 2 more Smart Citations
“…SHIP-1 was first shown to associate with immunoreceptor tyrosine-based inhibitory motifs of inhibitory FcRIIB, which indicated that it normally inhibits phagocytosis [92]. SHIP-1 has recently been shown to associate with FcR containing ITAMs [17,93]; it is therefore possible that it contributes to phagosome formation by turning off PI(3,4,5)P 3 -dependent signals in the forming phagosome.…”
Section: Phagosomal Lipidsmentioning
confidence: 99%
“…Syk signaling is required for efficient phosphorylation of the p85 regulatory subunit of phosphatidylinositol 3-kinase (PI-3K) [14], which activates the PI-3K catalytic subunit p110␤ [15], generating PI-3,4,5-trisphosphate [PI(3,4,5)P 3 ] from PI-4,5-bisphosphate [PI(4,5)P 2 ] in the membrane near the receptor complex. Other proteins recruited to the FcR complex include the protein phosphatase Src homology 2 (SH2)-containing tyrosine phosphatase-1 [16,17], Gab2 [18], SH2 domain-containing leukocyte phosphoprotein of 76 kDa [19], Cbl, Nck [20], and the 5Ј PI phosphatase, SH2 domain-containing inositol phosphatase 1 (SHIP-1) [17,21].…”
Section: Fcr and Associated Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…This reduces the ability of certain pleckstrin homology-containing proteins involved in mediating activation signals to target to the plasma membrane and become activated (14). Although SHIP1 has been studied extensively in the context of inhibitory FcRs (15,16), its role in NK cell responses initiated by the activation of FcgRIIIa is less well understood. Of note, Galandrini et al (17,18) have shown that FcgRIIIa cross-linking on primary human NK cells induced transient translocation of SHIP1 into lipid raft microdomains, where it associated with the~-chain of the FcR complex and negatively regulated antibody-dependent cellular cytotoxicity (ADCC).…”
Section: Introductionmentioning
confidence: 99%
“…SHP-1, which is mainly expressed in hematopoietic and less in epithelial cells, predominantly acts as a negative regulator of cellular signaling pathways induced by transmembrane receptors such as EpoR, c-Kit, and Fc␥RIIb1 (5)(6)(7)(8). In contrast, the ubiquitous SHP-2 is a positive regulator in the signal transduction of receptors like insulin receptor, platelet-derived growth factor receptor and EpoR (2)(3)(4)9).…”
mentioning
confidence: 99%